Validation of the Spanish-language version of the Montreal Cognitive Assessment as a screening test for cognitive impairment in multiple sclerosis - Gomez-Moreno, S.M.; Cuadrado, M.L.; Cruz-Orduña, I.; Martínez-Acebes, E.M.; Gordo-Mañas, R.; Fernández-Pérez, C.; García-Ramos, R. (Neurología (Barcelona, English ed. ), 2022)
The neuropsychological batteries traditionally used for the assessment of cognitive impairment (CI) in patients with multiple sclerosis are complex tests requiring a long time to administer. Simpler tests are needed to detect cognitive impairment in daily clinical practice. We aimed to evaluate the diagnostic validity and reliability of the Montreal Cognitive Assessment (MoCA) test as a screening tool for CI in patients with multiple sclerosis, as compared against the Brief Neuropsychological Battery. We recruited 52 patients with multiple sclerosis (61.5% women; mean age [standard deviation]: 41.7 [11.5] years). We analysed the reliability (internal consistency, interobserver reliability, and test-retest reliability), construct validity (factor analysis, Pearson correlation coefficient, and coefficient of determination), and criterion validity (ROC curve, sensitivity, specificity, total agreement, positive and negative predictive values, positive and negative likelihood ratios, and Fagan nomogram) of the MoCA test in this population. The prevalence of CI was 21.2% according to findings from the Brief Neuropsychological Battery, and 25% according to the MoCA test. The MoCA test showed good internal consistency (Cronbach alpha, 0.822) and interobserver and test-retest reliability (intraclass correlation coefficient 0.80 and 0.96, respectively). The correlation coefficient between total Brief Neuropsychological Battery and MoCA test scores was 0.82. The optimal cut-off point on the ROC curve was 25-26, yielding 91% sensitivity and 93% specificity. The MoCA test is a valid and reliable tool for screening for CI in patients with multiple sclerosis. Las baterías neuropsicológicas empleadas tradicionalmente para el diagnóstico del deterioro cognitivo (DC) en la esclerosis múltiple son pruebas complejas que conllevan mucho tiempo. Se necesitan test más simples para detectar el DC en la práctica clínica diaria. Evaluar la validez diagnóstica y la fiabilidad de la escala Montreal Cognitive Assessment (MoCA) como herramienta de cribado de DC en la esclerosis múltiple frente a la Batería Neuropsicológica Breve. Se seleccionaron 52 pacientes (61,5% mujeres, edad media [desviación estándar] 41,7 [11,5] años). Se analizaron la fiabilidad (consistencia interna, interobservador y test-retest) y la validez de constructo (análisis factorial, coeficiente de correlación de Pearson y coeficiente de determinación) y de criterio (curva ROC, sensibilidad, especificidad, acuerdo global, valores predictivos positivo y negativo, cocientes de probabilidad positivo y negativo y nomograma de Fagan). La prevalencia de DC fue del 21,2% según la Batería Neuropsicológica Breve y del 25% según el MoCA. El MoCA mostró buena consistencia interna (alfa de Cronbach 0,822) y buena fiabilidad interobservador y test-retest (coeficiente de correlación intraclase de 0,80 y 0,96, respectivamente). El coeficiente de correlación entre la puntuación total de la Batería Neuropsicológica Breve y el MoCA fue de 0,82. El punto óptimo de corte en la curva ROC fue 25-26, con una sensibilidad del 91% y una especificidad del 93%. El MoCA es una herramienta de cribado válida y fiable para la detección de DC en pacientes con esclerosis múltiple.